原式=-(1/3sinx^2+sinx*cosx+3/4cosx^2)+1=-(1/根号3sinx+根号3/2cosx)+1;sinx^2+cos^2=1,sinx/cosx=2得sinx=2/根号5,cosx=1/根号5得11/60
tanx=2 求2/3sinx^2+1/4cosx^2-sinxcosx
2个回答
相关问题
-
若tanx=2,求:(1)[4sinx−2cosx/5cosx+3sinx];(2)[sinxcosx1+cos2x
-
已知tanx=2,计算(1)sinx+2cosx/3cosx-4sinx;(2)1/2sinxcosx
-
tanx=-1/3 求3sinx^2+2sinxcosx-cosx^2的值
-
求证1-2sinxcosx/(cosx)^2-(sinx)^2=1-tanx/1+tanx
-
已知tanx=1/2,求(sinx+3cosx)/(sinx+cosx)和sin^2x+sinxcosx+2的值
-
证明(1-2sinxcosx)/(cosx-sinx)=(1-tanx)/(1+tanx)
-
求证(sinx)^2 tanx+ (cosx)^2 cotx + 2sinxcosx = tanx+cotx
-
tanx=2求2/3sinx²+1/4cosx²
-
已知tanx+4cotx=4求(sinx^3-2cosx)/(sinx+2cosx)
-
已知tanx=-2,求(3sinx-2cosx)/(5sinx+4cosx)=